Fundamentals of Entrepreneurship ENT 300 : DSR EXPRESS / Muhammad Ridzuan Mohd Rashid, Muhammad Nazrin Syafie Baharin and Muhammad Ammar Abu Bakar - Mohd Rashid, Muhammad Ridzuan; Syafie Baharin, Muhammad Nazrin; Abu Bakar, Muhammad Ammar (2021)
This business is established by 3 dedicated and ambitious individuals which hold important positions consist of General Manager, Administration Manager, and Operational Manager . To ensure that our service is of high quality and that our targeted clients receive a variety of products, we conducted a thorough and well-thought-out analysis. We expected to grow revenues in the first year of operation with more than one location because we have new and modern concepts as a major part of our business. There are a lot of delivery firms out there right now, but none of them do what we do. Our services offers delivery that focuses on rural areas especially for elderly and disabled. In addition, our services are not only focused on food and purchases through the platform but it also covers items that can be found in the market as well as medicines. Furthermore, our site is in a highly attractive and strategic location, as it is situated between the city road and the village area at No 19&18 Jalan Damai, Taman Damai, 42700, Selangor. The rural community in this area has access to this location. In the first year of our operation, we target a variety of local people as possible customers. According to a review of our competitors, we will face two or more firms that provide delivery services within a 10-mile radius of our premise location. Their enterprises will pose a challenge to ours because they have been in operation for years and have amassed a large number of devoted customers as a result. However, we believe that with our determination, consistency, high-quality services, and reasonable price, we will be successful. We anticipate that our business will grow in the near future as a result of our innovation on existing delivery services, which will not only appeal to individuals but will also become a need due to the pandemic.